2021
DOI: 10.2147/idr.s310139
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in situ Hybridization (FISH) in the Microbiological Diagnostic of Deep Sternal Wound Infection (DSWI)

Abstract: Purpose Postoperative mediastinitis after cardiac surgery is still a devastating complication. Insufficient microbiological specimens obtained by superficial swabbing may only detect bacteria on the surface, but pathogens that are localized in the deep tissue may be missed. The aim of this study was to analyze deep sternal wound infection (DSWI) samples by conventional microbiological procedures and fluorescence in situ hybridization (FISH) in order to discuss a diagnostic benefit of the culture-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…It should be emphasized that FISHseq is unsuitable as a sole diagnostic tool due to the existing false-negative FISHseq results (n = 4) and the necessary determination of the antibiogram as well as the extent of bacterial resistance status, which so far can only be elaborated by cultural evaluation. 49 Another meaningful advantage of FISHSeq is the ability to detect the microorganisms causing the infection in their biofilm environment without destroying the biofilm by manipulation. In the present work, we were able to detect the presence of an intact, mature biofilm in only three cases and nonplanktonic growth with a smaller number of colonies (microcolonies) in two other cases in the tissue samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasized that FISHseq is unsuitable as a sole diagnostic tool due to the existing false-negative FISHseq results (n = 4) and the necessary determination of the antibiogram as well as the extent of bacterial resistance status, which so far can only be elaborated by cultural evaluation. 49 Another meaningful advantage of FISHSeq is the ability to detect the microorganisms causing the infection in their biofilm environment without destroying the biofilm by manipulation. In the present work, we were able to detect the presence of an intact, mature biofilm in only three cases and nonplanktonic growth with a smaller number of colonies (microcolonies) in two other cases in the tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…In another four wounds, FISHseq confirmed the culture result, and it could be excluded (EXC, 8, 15, 44, 52) that the commensal pathogen detected by culture was a noncausative wound contamination. In 12 other wounds (12/53, 22.6%), one or more additional pathogens were detected by FISHseq (ADP, 16,20,22,24,31,37,38,41,48,49,50,59). In five wounds, it was also recognized that the pathogen detected was a nonplanktonic bacterial life form (NPF, 10, 34, 42, 50, 60).…”
Section: Specimen Collection and Bacterial Loadmentioning
confidence: 99%
“…This process may take more than 48 hours. 72 The biofilm may spread to different areas while waiting for the diagnosis results. Transmission electron microscopy (TEM), another method to visualize bacterial biofilms, could only be used to image ultra-thin samples.…”
Section: Current Methods Used For Biofilm Detection and Monitoring An...mentioning
confidence: 99%
“…Given their presence and pathogenic capacity, then it is unsurprising that fungi are important in chronic wound infections. While Candida is unlikely to play a significant role in these complex infections, it is frequently identified (19,79). Indeed, in culture‐based studies it has frequently been identified in diabetic foot ulcers (73,77).…”
Section: Candida Biofilms Are Important In Superficial and Deep Infec...mentioning
confidence: 99%